An Analysis of Cognitive Level in Reading Questions of English Textbook for Vocational High School - Andi Mega Januarti Putri; Rafiqa Rafiqa; Ainun Apriawan (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The paper intends to analyze the cognitive level of questions from the text in the English Textbook. The researchers examined the cognitive level of the reading questions and the most dominant level in this book based on the levels of the revised edition of Bloom's Taxonomy. Because the information gathered was verbal, this study can be classified as a qualitative descriptive. The researchers used the textbook "Look Ahead Book 1 An English Course" as a data source and uses a checklist table in collecting and analyzing data to find research results. The researcher analyzes the questions in an English textbook, but only focuses on questions from the text in the chapter with narrative text. After doing the research, there are 2 chapters containing narrative text questions and there are 61 questions that are studied.The results showed that the level of questions in the book "Look Ahead Book 1 An English Course" only contains 5 levels, namely Remembering, Understanding, Applying, Analyzing, and Evaluating, which from the research results found the percentage of each level is 11, 48% for the Remembering level, 16.39% for the Understanding level, 1.64% for the Applying level, 47.54% for the Analyzing level and 22.95% for the Evaluating level. Hence, In terms of Bloom's taxonomy, the Analyzing level is the most prevalent here, making up 47.54 percent of the text.